2020
DOI: 10.1002/jeq2.20011
|View full text |Cite
|
Sign up to set email alerts
|

Carbon mineralization, biological indicators, and phytotoxicity to assess the impact of urban sewage sludge on two light‐textured soils in a microcosm

Abstract: The agricultural reuse of urban sewage sludge (USS) modifies soil properties depending on sludge quality, management, and pedo‐environmental conditions. The aim of this microcosm study was to assess C mineralization and subsequent changes in soil properties after USS addition to two typical Mediterranean soils: sandy (Soil S) and sandy loam (Soil A) at equivalent field rates of 40 t ha−1 (USS‐40) and 120 t ha−1 (USS‐120). Outcomes proved the biodegradability of USS through immediate CO2 release inside incubati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 66 publications
0
8
1
2
Order By: Relevance
“…Sardans et al [71] pointed out that inputs of C, N, and P are the major processes that decide the stoichiometry of these nutrient elements in various ecosystems. Although SOC, TN, and TP contents were all altered by SS addition in our study, the decrease of C/N and increase of N/P indicated that microorganisms mineralized the organic carbon fractions and left a surplus N and enhanced P mineralization rate after SS was added to the soil [72].…”
Section: Responses Of Soil Properties To Ss Applicationcontrasting
confidence: 47%
“…Sardans et al [71] pointed out that inputs of C, N, and P are the major processes that decide the stoichiometry of these nutrient elements in various ecosystems. Although SOC, TN, and TP contents were all altered by SS addition in our study, the decrease of C/N and increase of N/P indicated that microorganisms mineralized the organic carbon fractions and left a surplus N and enhanced P mineralization rate after SS was added to the soil [72].…”
Section: Responses Of Soil Properties To Ss Applicationcontrasting
confidence: 47%
“…This can be particularly beneficial in drought conditions, as the soil can hold more moisture, providing a reservoir for plant growth and reducing seasonal water stress. However, the presence of higher organic matter in sewage sludge can stimulate microbial populations, leading to increased microbial respiration and subsequent water consumption ( Hechmi et al., 2020 ). It clearly indicates that if the soil is already experiencing drought conditions, this increased demand for moisture could further stress crops and reduce their growth and yield potential.…”
Section: The Climate-nutrient Nexus: Managing Nutrient Inputs For Sus...mentioning
confidence: 99%
“…de matéria orgânica nativa e à maior atividade microbiana no meio. Em outras pesquisas, todavia, não foi identificada influência da textura do solo nas taxas de mineralização obtidas (HECHMI et al, 2020;MALUF et al, 2015).…”
Section: Influência Da Textura Do Solo Receptor Na Mineralização Da M...unclassified
“…A diferença não foi significativa para a dose de 40 t.ha -1 de lodo, foi significativa quando aplicada uma dose de 120 t.ha -1 . Hechmi et al (2020) (1) taxa de mineralização média indicada nos estudos; (2) LAS: lodos aeróbios; (3) LAN: lodos anaeróbios; (4) NT: nitrogênio total. Fonte: Elaboração dos autores, 2022.…”
Section: Influência Da Textura Do Solo Receptor Na Mineralização Da M...unclassified